2008
DOI: 10.1016/j.dnarep.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and sequence-dependent activity of the Saccharomyces cerevisiae 3-methyladenine DNA glycosylase (Mag)

Abstract: DNA glycosylases initiate base excision repair by first binding, then excising aberrant DNA bases. S. cerevisiae encodes a 3-methyladenine (3MeA) DNA glycosylase, Mag, that recognizes 3MeA and various other DNA lesions including 1,N 6 -ethenoadenine (εA), hypoxanthine (Hx) and abasic (AP) sites. In the present study, we explore the relative substrate specificity of Mag for these lesions and in addition, show that Mag also recognizes cisplatin cross-linked adducts, but does not catalyze their excision. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
(80 reference statements)
3
12
0
Order By: Relevance
“…To determine if our assay was biased for the repair of particular alkyl lesions, we tested three glycosylases differing in their substrate specificities. E. coli TAG repairs 3MeA almost exclusively, sc MAG repairs a broad range of substrates, and sp Mag1 repairs several methylpurine lesions but with less efficiency than the other two [10,13,16,30,31]. We found that in this assay resistance to MNNG toxicity closely paralleled the reported 3MeA repair capacity of the glycosylase expressed, with comparable levels of MNNG protection for both E. coli TAG and sc MAG and decreased resistance for sp Mag1 (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…To determine if our assay was biased for the repair of particular alkyl lesions, we tested three glycosylases differing in their substrate specificities. E. coli TAG repairs 3MeA almost exclusively, sc MAG repairs a broad range of substrates, and sp Mag1 repairs several methylpurine lesions but with less efficiency than the other two [10,13,16,30,31]. We found that in this assay resistance to MNNG toxicity closely paralleled the reported 3MeA repair capacity of the glycosylase expressed, with comparable levels of MNNG protection for both E. coli TAG and sc MAG and decreased resistance for sp Mag1 (Fig.…”
Section: Resultssupporting
confidence: 75%
“…By contrast, the Saccharomyces cerevisiae ortholog, sc MAG, is inducible, repairs a broader set of alkylation lesions than sp Mag1, and its deletion has a profound effect on S. cerevisiae alkylation resistance, similar to E. coli alkA [4,1316]. Thus, constitutively expressed 3MeA glycosylases tend to have narrower substrate specificity and less overall impact on alkylation resistance than inducible ones.…”
Section: Introductionmentioning
confidence: 99%
“…MAG1 transcription is induced following exposure to low doses of alkylating agents (Chen et al 1990), and the purified protein excises N 7 -methylguanine and N 3 -methyladenine (Chen et al 1989(Chen et al , 1990Berdal et al 1990), as well as N 3 -methylguanine, 1,N 6 -ethenoadenine, and hypoxanthine from DNA (Saparbaev and Laval 1994;Lingaraju et al 2008). Mag1 also releases normal bases, primarily guanine, at a slow rate from intact DNA (Berdal et al 1998), and overexpression of the protein confers a strong spontaneous mutator phenotype in cells unable to efficiently repair AP sites (Glassner et al 1998;Klapacz et al 2010).…”
Section: Dna N-glycosylasesmentioning
confidence: 99%
“…TAG is constitutively active and highly specific for 3mA and 3mG, whereas AlkA is induced as part of the adaptive response to alkylation exposure and shares AAG’s broad substrate preference [1, 17]. Similar to AlkA, Saccharomyces cerevisiae Mag is inducible, lacks specificity for any particular alkylpurine, and exhibits a strong mutator phenotype [1821]. …”
Section: Introductionmentioning
confidence: 99%